Cascading Photoelectric Detecting and Chemiresistive Gas‐Sensing Properties of Pb5S2I6 Nanowire Mesh for Multi‐Factor Accurate Fire Alarm. Issue 8 (22nd June 2022) - Huang, Gui‐Qian; Jin, Ying‐Xue; Luo, Shao‐Zhen; Fu, Zhi‐Hua; Wang, Guan‐E; Xu, Gang
Abstract: Accurate fire warning is very important for people's life and property safety. The most commonly used fire alarm is based on the detection of a single factor of gases, smoke particles, or temperature, which easily causes false alarm due to complex environmental conditions. A facile multi‐factor route for fabricating an accurate analog fire alarm using a Pb5 S2 I6 nanowire mesh based on its photoelectric and gas‐sensing dual function is presented. The Pb5 S2 I6 nanowire mesh presents excellent photoelectric detection capabilities and is sensitive to ppm‐level NO2 at room temperature. Under the "two‐step verification" circuit of light and gas factors, the bimodal simulation fire alarm based on this Pb5 S2 I6 nanowire mesh can resist the interference of complex environmental factors and effectively reduce the false alarm rate. Abstract : Due to the excellent photoelectric detection capabilities and sensitivity to ppm‐level NO2 at room temperature, a facile multi‐factor route is presented to fabricate an accurate analog fire alarm using Pb5 S2 I6 nanowire mesh. Under the "two‐step verification" circuit of light and gas factors, the bimodal simulation fire alarm can resist the interference of complex environmental factors and effectively reduce the false alarm rate.